1994
DOI: 10.1017/s0950268800051645
|View full text |Cite
|
Sign up to set email alerts
|

A community outbreak of haemolytic-uraemic syndrome in children occurring in a large area of Northern Italy over a period of several months

Abstract: From March to October 1993, 15 cases of haemolytic-uraemic syndrome (HUS) in children were detected in a large area of northern Italy, where only 8 cases had occurred in the previous 5 years. Analysis of stool and serum specimens obtained from 14 cases showed evidence of Verotoxin-producing Escherichia coli (VTEC) infection in 13. Serum antibodies to the E. coli O157 lipopolysaccharide (LPS) were found in 8 patients and to the O111 LPS in 2. An O86 VTEC was isolated from another patient. Fourteen children need… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 22 publications
2
15
0
1
Order By: Relevance
“…Other workers have reported that classical EPEC strains possess alpha or beta intimin, whereas E. coli O86 isolates are commonly positive for epsilon intimin (1,42). The presence of gamma-like intimin in the isolates described in this paper confirms not only the heterogeneity of this serotype (13,34,57) but also the heterogeneity of the family of intimin proteins (1). It is possible that intimins, which are outer membrane proteins, may be subjected to strong selective pressure for amino acid diversity, either through adaptive shifts in tropism or through antigenic shifts to evade the immune system (42).…”
Section: Vol 68 2002 E Coli Isolates Possessing Gamma-like Intiminsupporting
confidence: 75%
“…Other workers have reported that classical EPEC strains possess alpha or beta intimin, whereas E. coli O86 isolates are commonly positive for epsilon intimin (1,42). The presence of gamma-like intimin in the isolates described in this paper confirms not only the heterogeneity of this serotype (13,34,57) but also the heterogeneity of the family of intimin proteins (1). It is possible that intimins, which are outer membrane proteins, may be subjected to strong selective pressure for amino acid diversity, either through adaptive shifts in tropism or through antigenic shifts to evade the immune system (42).…”
Section: Vol 68 2002 E Coli Isolates Possessing Gamma-like Intiminsupporting
confidence: 75%
“…A puzzling incident was reported from northern Italy, where 15 cases of HUS, caused by serotype O157 and other EHEC serotypes, was recorded over a 5-month period in 1993 (17). These cases occurred in small towns scattered over a large area with little apparent connection to each other; therefore, common food vehicles and exposure to cattle were eliminated as possible sources of infection.…”
Section: Other Vehicles Of Transmissionmentioning
confidence: 99%
“…The prevalence of E. coli O157 carriage in North American and European cattle varies according to the country and the detection method, ranging from 0 to 10% (1,8,11,12,13). In Italy, strains of E. coli belonging to serogroup O157 have been isolated from cattle in some northern regions (4,9), where human cases of hemolytic-uremic syndrome have been observed (7,21). In southern Italy, isolations from neither cattle of local farms nor humans have been reported so far.…”
mentioning
confidence: 99%